Prethermal Phases of Non-equilibrium Matter in Long-range Interacting Systems - Machado, Francisco; Else, Dominic V.; Kahanamoku-Meyer, Gregory D.; Nayak, Dr. Chetan; Yao, Norman Y. (2019 arXiv: Statistical Mechanics, 2019)
We prove the existence of non-equilibrium phases of matter in the prethermal regime of periodically-driven, long-range interacting systems, with power-law exponent , where is the dimensionality of the system. In this context, we predict the existence of a disorder-free, prethermal discrete time crystal in one dimension – a phase strictly forbidden in the absence of long-range interactions. Finally, using a combination of analytic and numerical methods, we highlight key experimentally observable differences between such a prethermal time crystal and its many-body localized counterpart.